2001
DOI: 10.1017/s1357729800055892
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary urea on embryo development in superovulated donor ewes and on early embryo survival and development in recipient ewes

Abstract: The aim was to examine the effect of dietary urea on yield and quality of embryos in superovulated donor ewes, and on embryo survival in recipient ewes. Ewes (25 donors and 34 recipients) were offered 1·25 kg of grass meal containing 50 g urea per ewe per day on a group basis; the remaining ewes (30 donors and 32 recipients) received 1·25 kg untreated grass meal per day. After 5 days, ewes were synchronized using a progestagen pessary for 14 days and stimulated with pregnant mare serum gonadotropin. Donors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Circulating urea has been negatively associated with fertility. (McEvoy et al, 1997;Fahey et al, 2001;Ferreira et al, 2011), except for Westwood et al's (1998) study. The detrimental effects on reproduction may be mediated in part through the direct effect of urea on the nuclear and cytoplasmic development of the follicle-enclosed oocyte (Santos et al, 2009;Ferreira et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating urea has been negatively associated with fertility. (McEvoy et al, 1997;Fahey et al, 2001;Ferreira et al, 2011), except for Westwood et al's (1998) study. The detrimental effects on reproduction may be mediated in part through the direct effect of urea on the nuclear and cytoplasmic development of the follicle-enclosed oocyte (Santos et al, 2009;Ferreira et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been suggested that such uterine environments are also hostile for the viability and motility of spermatozoa (Westwood et al 1998). Interestingly, Fahey et al (2001) found reduced embryo quality in donor ewes fed high‐protein diets, but the diet of the embryo recipients had no effect on survival of transferred embryos. Hence, they suggested that the adverse effects of urea on embryo quality are likely to be due to deleterious alterations in the environment of the follicle and/or oviduct, rather than due to a changed uterine environment (Fahey et al 2001; Papadopoulos et al 2001).…”
Section: High Milk Production Via An Elevated Crude Protein Intake Anmentioning
confidence: 97%
“…Interestingly, Fahey et al (2001) found reduced embryo quality in donor ewes fed high‐protein diets, but the diet of the embryo recipients had no effect on survival of transferred embryos. Hence, they suggested that the adverse effects of urea on embryo quality are likely to be due to deleterious alterations in the environment of the follicle and/or oviduct, rather than due to a changed uterine environment (Fahey et al 2001; Papadopoulos et al 2001). This finding was very recently confirmed in a study of lactating dairy cows (Rhoads et al 2006).…”
Section: High Milk Production Via An Elevated Crude Protein Intake Anmentioning
confidence: 97%
“…Urinary urea contributes to environmental pollutants, such as atmospheric ammonia and nitrates in ground water (Tamminga, 1992). Excess RDP can also have negative consequences for the ruminant; excess RDP reduces embryo quality in sheep, possibly related to ovarian steroid concentrations affecting embryo development and transport (Berardinelli et al, 2001;Fahey et al, 2001).…”
Section: Introductionmentioning
confidence: 99%